The Screaming Middle: A Memoir in Verse of a Very Strange Year - Bradley Smith, Susan (2016)
This is a memoir of a woman turning 50 who forgot to have a party. It takes you on road trips, into psych wards, into the chambers of marriage and through epic failures, brilliant ideas and back to kingdoms of chaos and castles of hilarity. There’s a lot of bitching and loving, a lot of fights and great nights. It’s Orwellian in its frank and unforgiving expedition through life’s hardships and glories. If you thought you needed Little Golden Books when you were young then think no more about trading up to the solid gold of The Screaming Middle: the novel cure we all need.